Analysis of design patterns for educational application development: serious games (2020)
Learning based on serious games is an emerging field in education, product of the proliferation of technological aids in the educational field and the necessary opening to new didactic methods that support the educator in the complexity of joining the transmission of knowledge and in the training in competences that comprise the learning process. In recent years, there has been a remarkable set of experiences in applying game-based learning to formal training scenarios, particularly in the higher education environment, which have encouraged the attempt to develop a working tool designed for the development of one of the most complex competences of the learning process and, at the same time, contradictory to individualism: teamwork. In this study, a serious game has been designed, with the aim of promoting and analyzing the development of teamwork skills. In this serious game, students have to solve a problem whose solution depends mainly on the ability to negotiate among group members.